X-men: messiah complex ebook Messiah complex - special. - Various (Marvel Worldwide, Inc., 2011)
Collects X-Men: Messiah Complex One-Shot, Uncanny X-Men (1963) #492-494, New X-Men (2004) #44-46, X-Men (2004) #205-207, X-Factor (2005) #25-27. The first mutant since HOUSE OF M has arrived. Will she bring salvation or destruction to the X-Men and all mutankind?